The effect of low oveerall equipment effectiveness (OEE) on working hours and production costs of supplement products - Devilke Yandriyani; Maura Linda Sitanggang; Indah Masri (Jurnal Info Sains : Informatika dan Sains, 2024)
The pharmaceutical industry has strict regulations and procedures to guarantee a quality system by implementing Good Manufacturing Practices (CPOB) or current Good Manufacturing Process (cGMP). This must be adhered to by the pharmaceutical industry to ensure the safety, efficacy and consistent quality of the products produced. To produce consistent quality, the pharmaceutical industry needs to make continuous or ongoing improvements, one of the improvements that must be made is reducing downtime and reducing defective products. These improvements will increase the effectiveness of the machine. One method that can be used is Overall Equipment Effectiveness (OEE). This research aims to determine the effect of OEE values on working hours and production costs (direct labor & factory overhead) of supplement products by looking at the differences between actual and standard. This research uses descriptive quantitative methods followed by qualitative methods to find the root of the problem. Quantitative by calculating the value of availability level, performance level, quality level, OEE value, working hours and production costs (direct labor & factory overhead). Qualitative with Focus Group Discussion (FGD). The primary packaging production process for supplement products in 2022 shows an availability level of 47.23%, a performance level of 82.50%, a quality level of 95.78%, an OEE value of 37.32%. This shows that the condition of packaging machine X is not in prime condition because the overall OEE value is still below the ideal value of 85%. The low OEE value has an impact on working hours and production costs (direct labor & factory overhead) where the T test results show a significant difference between standard and actual (p-value (1.2829x10-6) ≤ α (0.05).